Choice of temporary contraception based on client’s demographic status and parity - Pandit, Benju (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aim: To analyse the demographic factors and parity in women influencing choice of contraceptive methods. Methods: This is a hospital record based retrospective study at Bhaktapur hospital, a tertiary hospital in a span of 6 months from October 2020 to March 2021. Data were collected from medical record and descriptive analysis was done. Results: There were 142 women taking contraceptive service in six months.Implant was the most commonly used method of contraception (48%), followed by the IUCD (26%), Injectable (16%) and OCP (10%). Age group of 20-39 had more acceptance of contraception as compared to adolescent and women above 40. More the parity more usage of long acting reversible contraception was found. Conclusion: The most common contraceptive method used among women was implant. Client having two or more children are more to receive long acting contraception.